Antioxidant Activity Test of Barangan Banana Peel (Musa Acuminata Linn) Etanol Extract With DPPH Method - Arista, Nurul; Siregar, Rudi Munzirwan (Universitas Negeri Medan, 2023)
Barangan banana (Musa acuminata linn) is also called Medan banana which is often found in North Sumatra. Banana peels are known to contain phenolic compounds that have potential as antioxidants. This study aims to determine the antioxidant activity of raw and ripe banana peel extract of Barangan banana (Musa acuminata linn) using the DPPH (1,1-diphenyl-2-pikrihidrazil) method. The data obtained was calculated to determine the antioxidant activity. The results showed that the antioxidant activity of the ethanol extract of Barangan raw banana peel IC50 = 32,52 μg/mL, the ethanol extract of Barangan ripe banana peel IC50 = 83,60 μg/mL, and the vitamin C comparator obtained an IC50 value of 5,00. Raw banana peel extract has higher antioxidant activity than ripe banana peel extract.